Metal-enhanced photoluminescence from carbon nanodots - zhang, yx (2011)
In the last couple of years, carbon dots have emerged as a new novel luminescent particle for applications in fluorescence and microscopy in some ways analogous to quantum dots and silicon nanocrystals/particles. As with any fluorescent label or tag, absolute fluorescence intensity, brightness, and particle photostability are a primary concern. In this communication we subsequently show that similar to classical fluorophores, carbon dots located in the near-field, near to Plasmon supporting materials, show enhanced intensities and improved photostabilities.